Moving from reclusion to partial freedom: the experience of family caregivers for disabled elderly persons assisted in a day care center - Bocchi, Silvia Cristina Mangini [UNESP]; Cano, Karen Cristina Urtado [UNESP]; Baltieri, Lilian [UNESP]; Godoy, Daniele Cristina; Spiri, Wilza Carla [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP] (Associação Brasileira de Saúde Coletiva (ABRASCO), 2010)
O estudo teve como objetivos: compreender a experiência interacional cuidador familiar-idoso dependente apoiada por um Centro-Dia (CD), segundo a perspectiva do cuidador familiar, e desenvolver um modelo teórico representativo da experiência vivida por ele. Utilizou-se como referencial metodológico a Grounded Theory e como referencial teórico o Interacionismo Simbólico. As estratégias para a obtenção dos dados foram a observação e a entrevista. Dos resultados emergiu o fenômeno: sentindo-se apoiado pelo CD, pela força do vínculo com o idoso e pela espiritualidade para continuar desempenhando o papel desafiante de cuidador familiar de idoso dependente. O trabalho permitiu-nos compreender que dentre esses três pilares de apoio para enfrentamento da sobrecarga gerada pelo papel de familiar cuidador dependente, o modelo assistencial promovida pelo CD é o que se configurou como variável interveniente no processo de melhora da qualidade de vida do binômio cuidador familiar-idoso dependente. Isto nos possibilitou identificar a categoria central - movendo-se da reclusão à liberdade parcial: a experiência do cuidador familiar de idoso dependente assistido num CD.

This study aimed at understanding the interactional experience between family caregivers and disabled elderly persons supported in a Day Care Center according to the caregiver's perspective. It also aimed at developing a representative theoretical model for the events experienced by such caregiver. The Grounded Theory was used as methodological framework whereas Interactional Symbolism served as the theoretical framework. Observation and interviews were used for data collection. The following phenomenon arose from the results: feeling of support by the Day Care Center, by the strength of the bond with the elderly and by spirituality in order to continue playing the challenging role of a family caregiver for a disabled elderly person. The study made possible to understand that, among these three supporting cornerstones for coping with the burden generated by the family caregiver role, the care model promoted by the Day Care Center was the intervenient variable in the process of improving the quality of life of the family caregiver-disabled elderly person binomial. This allowed the identification of the main category - moving from reclusion to partial freedom: the experience of family caregivers for disabled elderly persons assisted in a Day Care Center.
Movendo-se da reclusão à liberdade parcial: a experiência do cuidador familiar de idoso dependente assistido num centro-dia
Keywords: Idoso; Família; Assistência diurna; Elderly; Family; Day care